Investigating The Nexus Between Sustainable Banking And Economic Development In India: An Empirical Analysis Using The ARDL Model - Sugyani Rath, Kishore Kumar Das (European Economic Letters (EEL), 2025)
Purpose: This study investigates the dynamic determinants of sustainable banking in India by constructing a Sustainable Banking Performance Index (SBPI) and modelling its interactions with macro-financial and environmental drivers. Design/methodology/approach: Using secondary data for 2005–2024 from RBI, SEBI (BRSR), World Bank, IMF, UNCTAD, BIS and Refinitiv ESG, the analysis employs the ARDL bounds approach. Stationarity is assessed via ADF and PP tests; cointegration is evaluated through bounds F-statistics; short-run adjustment is captured by an ECM. Diagnostics include Breusch–Godfrey, Breusch–Pagan, Jarque–Bera and Ramsey RESET; parameter stability is examined with CUSUM/CUSUMQ. The dependent variable is SBPI (composite of green credit growth, ESG disclosure and banking stability); regressors are green credit growth, NPA ratio, FDI inflows, GDP per-capita growth, carbon emissions, and stock-market liquidity. Findings: Results indicate cointegration between SBPI and its determinants. In the long run, green credit, FDI, GDP growth and market liquidity positively influence SBPI, while NPAs and carbon emissions exert significant negative effects; short-run dynamics are directionally consistent. The error-correction term (≈−0.61) implies rapid convergence. Residual tests indicate no serial correlation or heteroskedasticity, normal errors and correct specification; CUSUM/CUSUMQ confirm stability. Practical implications: Strengthening green-credit taxonomies, integrating climate stress-testing and financed-emissions disclosure, and deepening capital markets can accelerate sustainable banking. Reducing NPAs and supporting transition finance are essential. Originality/value: The paper develops a novel SBPI and provides ARDL-based evidence for India, linking sustainability to macro-financial conditions and environmental pressure. Limitations relate to proxy-based measurement and potential structural breaks; future work may incorporate primary data, threshold effects, and BRICS comparisons.